Obraz dawnego powiatu husiatyńskiego w świetle nazw miejscowości - Czapla, Anna (Slavia Orientalis, 2024)
Onomastic Picture of the Husiatyn District in the Podolian Voivodeship of the First Polish-Lithuanian Commonwealth. The Husiatyn District with the western part of Podolia were joined to Poland in the 14th century, to which it belonged intermittently until the end of World War II. The purpose of the article is a semantic and structural analysis of the area’s place names, on the basis of which emerges a linguistic picture of the Husiatyn District. The most numerous group of physiographic names describes its natural properties – the richness of its rivers and lakes, the animals living there, forested places, numerous undulations and plateaus. Also, ethnic names indirectly refer to the nature of the land itself, whereas cultural names describe the district due to the properties acquired as a result of human activity. The most recent layer are the ideological names created during communism. Older cultural names inform of settlement forms, defensive places, places related to the economy. Renewed and diminutive names depend on the new settlements being built in the area. Among the names of places derived from personal names, the most numerous group are patronymic names, which are based on eastern or neutral names, just as with the possessive.